Boosting the Oxygen Reduction Performance via Tuning the Synergy between Metal Core and Oxide Shell of Metal−Organic Frameworks‐Derived Co@CoOx. Issue 7 (11th March 2020) - Wang, Hao; Kou, Rong‐Hui; Jin, Qiu; Liu, Yu‐Zi; Yin, Feng‐Xiang; Sun, Cheng‐Jun; Wang, Liang; Ma, Zhi‐Yuan; Ren, Yang; Liu, Ning; Chen, Biao‐Hua
Abstract: Co core@Co oxide shell (Co@CoOx ) catalysts represent a large family with promising oxygen reduction reaction (ORR) catalytic activity. However, inadequate understanding of Co@CoOx synergy prohibits further pursuit of catalytic performance enhancement. Herein, a Co zeolitic−imidazolate framework was converted into metallic Co, followed by controlled air treatment to form Co@CoOx . The composition and structure evolution as a function of air treatment temperature were studied thoroughly through conventional and synchrotron (both ex‐situ and in‐situ) characterizations, confirming the coexistence of CoO and Co3 O4 in the shell. The optimal catalyst showed an ORR half‐wave potential of 0.87 V (vs. RHE) in an alkaline half‐cell and delivered high discharge capacity in an aprotic Li−O2 battery (7, 124 mAh gCat+C −1 ) and an aqueous Zn−air battery (694 mAh gZn −1 ) with good performance retention after durability test. Modeling simulation and density functional theory calculation confirmed the charge donation from metal core to oxide shell and shed light on new insights of how metal@metal oxide synergy impacted the ORR via tuning the charge conductivity, oxygen affinity and intermediate transfer pathway. This work opens up a venue to boost ORR catalytic activity from an interfacial synergy perspective. Abstract : Fine tuning : Charge donation from metallic Co core to Co oxide shell is verified in a metal−organic framework‐derived Co@CoOx system, enabling the surface of Co oxide more electron enriched. Such synergy alters the charge conductivity, oxygen affinity, and intermediate transfer mechanism during the ORR. Adequate understanding of such correlations aids in further improving the activity of Co@CoOx ORR catalysts.